(untitled) (International relations and international law Journal, 2016)
The article discusses the democratization of society and its impact on the combating terrorism. The author believes that the problem of democratic development and democratization, which combines domestic and foreign policy issues, promote sustainable development and security. The potential instability in Central Asian region remains with a whole set of problems, many of them are related to the issue of genuine democratization in Central Asia. A stable society, promoting human right, is the best protection against strengthening terrorist groups. The author of the article argues with the idea that the absence of democracy promotes terrorism. Terrorist groups also operates in developed democracies. For example, the terrorist attacks on the United States of America from outside and inside the country.